Leachate Treatment by Applying M.B.B.R Technology with Manufactured Additive from Agricultural Waste and Filtration through Brick Scraps - Mohamed Nabil Ali, Hanan A. Fouad, Ahmed Hossam El-Din Helmy, Rehab M. El-Hefny (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Sanitary landfilling is one of traditional effective method in solid waste disposal. The solid waste dumped in large pre-equipped area. The solid waste start to decompose to generate gases such as methane and also liquids such as leachate. The leachate is very serious environmental enemy especially for surface water, groundwater, and soil because it contains a sever contaminants such as toxic matters and heavy metals. Leachate treatment methods used globally such as activated sludge, sequential batch reactor and moving bed biofilm reactors. The M.B.B.R method have been chosen to be used in this research as a result of high removal efficiency achieved. In this research we proposed a combination between biological treatment using moving bed biofilm reactor (M.B.B.R) and physical treatment through settling and filtration processes to enhance the leachate physiochemical properties to be used in irrigation purpose for minimizing the gap between fresh water requirements and raw water availability. The filtration process applied by using a brick scraps filter as applying recycled material usage concept. A micro scale pilot had been constructed for leachate treatment by using four rectangular glass tanks with total volume of 54 liters and working volume of 45 liters. The first tank is considered as primary settling tank. The second tank is M.B.B.R unit. The third tank is final settling tank. The last tank is collection tank and Preceded by brick scraps filtration column. A treatment additive had been manufactured by using agricultural waste such as sugarcane and palm leaf for enhancing the treatment efficiency. A numerous trial has been accomplished, till the satisfactory results achieved. Applying a 12-hour aeration cycle with adding a combination between sugarcane and palm leaf additives enhance the physiochemical parameters largely and the effluent is satisfying the environmental laws to be used in irrigation purposes. The removal efficiency of COD, BOD, TSS, NH3, TKN and TP reach 99.31%, 98.80%, 99.33%, 97.33%, 99.79% and 76.48%. All physiochemical testing had been conducted at the national research center.